Evidence based medicine is the conscientious, explicit, and judicious use of current evidence in making decisions about the care of individual patients - Komatsu, Ricardo Shoiti (São Paulo Medical Journal, 1996)
The 2nd. U.K. Workshop on Evidence Based Health Care, London, 11th-16th February 1996, with Dr.Trisha Greenhalgh (UCLMS) as co-ordinator, and Prof. David Sackett (Oxford), as orientator, constituted an important meeting to disseminate EBHC in UK and Europe. "Evidence Based Medicine is the conscientious, explicit, and judicious use of current best evidence in making decisions about the care of individuals patients" (Sackett, 1996). The methodology utilized was Problem-Based Learning (PBL), with small groups sessions with tutor and co-tutor as facilitators of the discussion process. The participants have been demonstrated that it’s possible to teach EBHC using different strategies, approaches and resources.This Workshop was an excellent opportunity not only to share and receive informations about Clinical Epidemiology, Biostatistics and EBHC, but also to participate in a "learning to learn" active process to understand how to teach and learn EBHC.